Hubungan Perilaku Merokok Dan Tingkat Stress Dengan Tekanan Darah Pada Pasien Hipertensi - Enjelika Dwi Amelia; Dwi Retno Sulistyaningsih; Retno Setyawati (An-Najat, 2025)
Hypertension is a global health issue that can lead to severe complications. Risk factors for hypertension include smoking behavior and stress levels, which are often overlooked. This study aims to evaluate the relationship between smoking behavior, stress levels, and blood pressure in hypertensive patients at Sultan Agung Islamic Hospital, Semarang. This study employed a correlational design with a cross-sectional approach. A total of 111 respondents were selected through purposive sampling. Smoking behavior was measured using the Glover Nilsson Smoking Behavior Questionnaire (GN-SBQ), while stress levels were assessed using the Perceived Stress Scale (PSS-10). Blood pressure was measured using a sphygmomanometer. Data were analyzed using Spearman Rank correlation. The results of this research are getting results the majority of respondents were heavy smokers (75.7%) and experienced severe stress levels (90.1%). The correlation between smoking behavior and blood pressure showed a very weak negative relationship and was not statistically significant (p > 0.05). Similarly, the relationship between stress levels and blood pressure was also not statistically significant (p > 0.05). The conclusion there is no significant relationship between smoking behavior or stress levels and blood pressure in hypertensive patients in this study. These findings highlight the importance of a holistic approach in managing hypertension